2015
DOI: 10.1123/jtpe.2013-0152
|View full text |Cite
|
Sign up to set email alerts
|

Middle School Teachers’ Strategies for Including Overweight Students in Skill and Fitness Instruction

Abstract: As part of a larger study, this paper describes teachers’ perspectives and strategies on including overweight and obese students (OWS) in instruction related to motor skill/game play and fitness development in physical education. Using the Social Ecological Constraints framework, a qualitative multicase study was conducted using multiple in-depth interviews, class observations, and artifacts from nine experienced and committed suburban middle school Physical Education teachers. Constant comparison was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…As such, the identity is possibly-but not necessarily-at odds with descriptions of a humiliating, stigmatizing physical education (Pausé, 2019;Sykes & McPhail, 2008) as well as general portrayals of physical educators as insensitive and as inclined to engage in anti-fat practices (Lynagh et al, 2015;Sirna et al, 2010). The identity is, on the other hand, closely aligned with the inclusive role advocated in recent, practicallyoriented scholarship (Rukavina et al, 2015;Tingstrom, 2015).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…As such, the identity is possibly-but not necessarily-at odds with descriptions of a humiliating, stigmatizing physical education (Pausé, 2019;Sykes & McPhail, 2008) as well as general portrayals of physical educators as insensitive and as inclined to engage in anti-fat practices (Lynagh et al, 2015;Sirna et al, 2010). The identity is, on the other hand, closely aligned with the inclusive role advocated in recent, practicallyoriented scholarship (Rukavina et al, 2015;Tingstrom, 2015).…”
Section: Discussionmentioning
confidence: 95%
“…Tingstrom (2015) considers how the needs of overweight students can be addressed in elementary physical education. Within this scholarship, physical educators take on the tasks of determining and meeting the needs of overweight students, creating safe and inclusive learning environments, and understanding barriers to participation (Rukavina, Doolittle, Li, Manson, & Beale, 2015;Stewart & Webster, 2018). In this way, obesity discourse produces caring custodian identities.…”
Section: Physical Education Teacher Identities and Obesity Discoursesmentioning
confidence: 99%
“…As part of a larger study, this paper reports on data related to any strategy teachers reported or used in PE to promote social inclusion of OWS, or tolerance or acceptance of individual differences or relationships, through teacher‐student and student‐student interactions, instructional tasks, or program policies. Other papers in this study focus on perceptions of OWS, their needs and individual interventions for them, and teachers' perspectives on instructional and curricular strategies for OWS' achievement of skill and fitness goals in PE . This paper is focused on strategies for including students socially, and the instructional settings and school level constraints that directly affect inclusion in PE instruction and positive social climate.…”
Section: Methodsmentioning
confidence: 99%
“…Teaching strategies related to caring for overweight students' wellbeing and adapting activities are frequently proposed (Li et al, 2017;Tingstrom, 2015). Different strategies of inclusion are used to reduce obstacles to participation, ensure a positive class climate, and provide a safe and positive experience (Cliff & Wright, 2010;Li et al, 2017;Rukavina et al, 2015;Stewart & Webster, 2018).…”
Section: A Pluralistic Discoursementioning
confidence: 99%
“…The role of PE here takes a clear critical position towards fat-phobia that is occurring 'at every corner of the gym' (Li & Rukavina, 2012, p. 312; see also Trout & Graber, 2009). It is argued that PE does a poor job of including overweight students (Rukavina et al, 2015) where teachers show implicit anti-fat attitudes and adhere to an ideology of blame i.e. that individuals are responsible for their weight and its negative consequences (Grenleaf & Weiller, 2005).…”
Section: Includingmentioning
confidence: 99%